Incorporating uncertainty and nonlinearity into the calculus of an efficient response to the threat of global warming. (4th August 2014) - Yohe, Gary; Garvey, Brendan
The possible serious social and economic consequences of global warming raise a series of questions. Some researchers have focused on the potential damage associated with global change; others have considered how such damage could be mitigated. Still others now investigate the range of uncertainty with which the future can be viewed. The fundamental policy and research issue straddles all of these more focused questions and calls for an integrated and dynamic analysis. This paper extends the Nordhaus framework, introduced in 1991, to address two omissions: the effect of cascading uncertainty across a variety of sources and the potential for severe nonlinearities in damages. The results suggest not only that more aggressive emission reduction strategies are in order, but also that it is appropriate for researchers to focus on emissions and potential damage trajectories which lie either above the mean or above the most likely scenario.